Evaluation of respiratory function indicators of elite athletes in academic rowing using the method of computer spirography - Omelchenko, O.; Dolbysheva, N.; Kovtun, A.; Koshcheyev, A.; Tolstykova, T.; Burdaiev, K.; Solodka, O. (Pedagogy of Physical Culture and Sports, 2023)
Background and Study Aim. In modern sports, the research and study of the functional capabilities of athletes' breathing is relevant. The analysis of individual results made it possible to form an idea about the respiratory functions of athletes. Among elite athletes, parameters of respiratory functions are significantly higher than the norm, so their interpretation relative to the general healthy population is inadequate. The purpose of the study is to determine lung volumes and dynamic parameters of the respiratory act and their difference in height and weight categories, respectively.